Competitive Capabilities and Business Performance among Manufacturing SMEs: Evidence from an Emerging Economy, Malaysia. Issue 1 (2nd January 2016) - Ho, Theresa C.F.; Ahmad, Noor Hazlina; Ramayah, T.
ABSTRACT: This study examines whether the manufacturing competitive capabilities that Malaysian small and medium enterprises (SMEs) in the manufacturing sector currently pursue yield satisfactory returns in terms of financial and nonfinancial performance. A sample of 145 manufacturing SMEs were analyzed to examine the relationship between manufacturing competitiveness (price, delivery dependability, innovation, and quality) and business performance (financial and nonfinancial) using partial least squares approach via Smart PLS 2.0. The study reveals that competitive capabilities did not lead to satisfactory financial performance. However, manufacturing competitive capabilities, in terms of delivery dependability and quality, did lead to satisfactory nonfinancial performance.